VO2max gene - Whithford-Cave, J.; Yu, B.; Cole, S.; Henderson, J.; Sawyer, N.; Trent, R. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
The cardiovascular system plays a central role in many sports, especially endurance type and VO2max is the main measurement of cardiovascular function. In this study, we attempted to identify the underlying gene(s) at the loci that have a suggestive linkage with VO2max in a genome-wide scan. Firstly, an in silico search was carried out to select plausible candidates, followed by association study using single nucleotide polymorphisms covering the candidate genes. We found a positive association between gene X and endurance athletic performance. Secondly, we analysed the exons (protein coding) and exonintron boundaries in eight amplicons (DNA amplified products) from representative DNA samples. After scanning through the amplicons using denaturing high performance liquid chromatography, we identified four DNA variants. One of the variants, a sequence variation near a splice site, was further genotyped in 367 elite endurance athlete samples consisting of cyclists, ironmen and rowers and 179 controls. The distribution of this DNA variant was not significantly different between endurance athletes and controls (p>0.05). Further analysis of the sub-group of Olympian endurance athletes versus controls was also not significant. However, the eight amplicons only cover small portion of the genomic region of gene X and hence a functional variant could be located in the regulatory regions other than exons or exon-intron boundary regions. The gene will be further characterized for the functional DNA variant that contributes to the identified positive association.